Multi-locus phylogeny and morphology support Phaeocytostroma saprophyticum sp. nov. in Diaporthales - Ding, Peng-Cheng; Madhushan, Asanka; Shami, Ashwag; Alharbi, Nada K.; Liu, Jian-Kui; Maharachchikumbura, Sajeewa S. N. (Phytotaxa, 2025)
A saprobic fungal specimen was collected from dead wood in Mianyang City, Sichuan Province, during a survey on fungal diversity. Preliminary BLAST analysis of the internal transcribed spacer (ITS) region indicated that the isolate belongs to the genus Pseudophaeocytostroma (Diaporthaceae). To determine its phylogenetic position, multilocus phylogenetic analyses were performed using sequences from the ITS, the large subunit ribosomal RNA (LSU), and the translation elongation factor 1-alpha (tef1-α) regions. The resultant phylogeny revealed that the isolate forms an independent clade that is closely related to “Phaeocytostroma sacchari” and Pseudophaeocytostroma bambusicola. Morphologically, our collection differs from its closest relative by the size of conidia and the abundance of paraphyses. Single-gene phylogenies revealed topological incongruence among loci in Diaporthaceae, indicating the need for caution when delimiting new species and generic placements. This underscores the importance of incorporating additional molecular markers or genomic data in future taxonomic revisions. Based on combined molecular evidence and morphological characteristics, we hereby introduce Phaeocytostroma saprophyticum as a novel species.